Response to reviews of 'Diagnosing Madness' - Cristina Hanganu-Bresch (Romanian Journal of Communications and Public Relations, 2021)
I want to thank the reviewers profusely for engaging so deeply and thoughtfully with our book, and for offering both generous assessments and thorough, well informed critiques. It has been two years since the book was published and four since my mentor and co-author passed away; it is, perhaps, a good time to reflect on it and respond to those who in good faith have parsed its ideas and placed them in proper historical and theoretical context.